Health assessment for migrants and asylum seekers upon arrival and while hosted in reception centres: Italian guidelines. Issue 3 (March 2021) - Tosti, Maria Elena; Marceca, Maurizio; Eugeni, Erica; D'Angelo, Franca; Geraci, Salvatore; Declich, Silvia; Della Seta, Maurella; Ferrigno, Luigina; Marrone, Rosalia; Pajno, Chiara; Pizzarelli, Scilla; Rosso, Annalisa; et al.
Highlights: Active case finding for TB, malaria, STD, intestinal parasites, diabetes, anaemia, pregnancy. Early identification of infections and diabetes among asymptomatic subjects, based on risk-conditions. Mass screening for non communicable diseases such as anaemia and hypertension. Integration into national healthcare routine services for cancer screening and vaccination programs. Continuity of health assessment and prevention during all stages of the reception pathways. Abstract: Background: During 2016–17, national guidelines were developed in order to provide evidence-based recommendations on health assessments for migrants and asylum seekers upon their arrival in Italy. Methods: Scientific literature published between 2005 and 2016 was searched in different databases. A free search was also performed on international organizations' websites in order to identify additional relevant documents. A multidisciplinary panel discussed the resulting evidence and formulated recommendations. Results: Evidence-based recommendations were formulated: signs and symptoms of specific diseases should to be actively searched for active TB, malaria, STI, intestinal parasites, diabetes, anaemia. In case of other health conditions (latent TB, HIV, HBV, HCV, STI, strongyloides, schistosoma, diabetes), testing should be offered to asymptomatic subjects coming from endemic areas or exposed to risk factors. Mass screening is recommended for anaemia and hypertension; a pregnancy test should be considered, while inclusion in cervical cancer screening and vaccination programs is recommended. A modulated, progressive approach was developed, covering an initial evaluation during rescue operations, a full medical examination at first line reception stage and the referral to national health services during second line reception. Conclusions: It is important to produce and periodically update guidelines on these issues and local peculiarities should be taken into account in their design and implementation. Guidelines can not only support economic sustainability, but also counteract stigmatization dynamics.